1997
DOI: 10.1093/geront/37.2.218
|View full text |Cite
|
Sign up to set email alerts
|

Gain in the Caregiving Experience: Where Are We? What Next?

Abstract: This critical review of 29 studies published through 1996 on the gain experienced among informal caregivers of older adults, identifies 13 conceptual (i.e., definitions and theoretical frameworks) and methodological (i.e., sampling, design, measurement, analysis) observations. Key limitations of prior research are highlighted and recommendations necessary for the advancement of research in this area of inquiry are made. Drawing upon relevant theoretical frameworks and the observations noted in this review, a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
397
2
26

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 521 publications
(463 citation statements)
references
References 72 publications
18
397
2
26
Order By: Relevance
“…The present findings also suggest that this component of problem solving is implicated in caregiver well-being. Many caregivers thrive in their role and experience personal fulfillment (Kramer, 1997). Perhaps caregivers who have a lower negative orientation are more inclined to find personal meaning in their activities, or alternatively, their caregiver experience (and their relationship with the care recipient) is not compromised by the distress and pessimism that typically characterizes a negative orientation.…”
Section: Overall Discussionmentioning
confidence: 99%
“…The present findings also suggest that this component of problem solving is implicated in caregiver well-being. Many caregivers thrive in their role and experience personal fulfillment (Kramer, 1997). Perhaps caregivers who have a lower negative orientation are more inclined to find personal meaning in their activities, or alternatively, their caregiver experience (and their relationship with the care recipient) is not compromised by the distress and pessimism that typically characterizes a negative orientation.…”
Section: Overall Discussionmentioning
confidence: 99%
“…In the present sample, about 88% of the informal caregivers provide care to a family member (partner, parent, children, sister, or brother). Previous research has shown that providing informal care to close family members involves a relatively larger negative subjective burden (both physically and emotionally) than providing care to non-family members (Hughes et al, 1999;Kramer, 1997). If this evidence is confirmed, a stronger inverse relationship between hours of provided informal care and well-being will be found for informal caregivers who are family of the care recipients than for informal caregivers who are not.…”
Section: The Well-being Modelmentioning
confidence: 94%
“…The relationship between income and well-being is expected to be positive, while the relation between hours of provided informal care and well-being is expected to be negative. The hypothesised negative relationship is mainly due to the opportunity cost of time of providing care and the involved negative subjective psychological and physical burden of providing care (Kramer, 1997). It is also possible that providing care has two positive effects on the caregiver's wellbeing.…”
Section: The Well-being Modelmentioning
confidence: 99%
“…In the past there has been criticism that interventions have conceptualised the carer role from a stress-coping perspective and this has led to a dominance of negative outcome measures such as stress, depression and burden. However, the last two decades have seen the introduction of the concept of positive aspects of caregiving (Grant and Nolan, 1993;Kramer, 1997). It has been suggested that psychosocial interventions should stress the positive aspects of caring and increasing positive events in order to maintain and improve carers' involvement.…”
Section: Introductionmentioning
confidence: 99%